Central sensitization - Woolf, Clifford (Henry Stewart Talks, 2009)
Clinical pain syndromes, What is responsible for the conversion of high threshold nociceptive pain to low threshold clinical pain?, Nociceptive pain, Neuronal plasticity, Inflammatory pain, Nociceptor sensitizors, Inflammation, Neuropathic pain, Dysfunctional pain, Treatment of clinical pain, Central sensitization, Secondary hyperalgesia/tactile allodynia, Activity-dependent central sensitization, Transcription-dependent central sensitization, Synaptic disinhibition, Structural synaptic plasticity, Neuroimmune interactions